Multichannel Target Detection for Maritime Radar - Aboutanios, Elias; Rosenberg, Luke (2019 53rd Asilomar Conference on Signals, Systems, and Computers, 2019)
Coherent target detection in a multichannel maritime radar is a challenging problem due to the dynamic nature of sea clutter. Traditional detectors, such as the adaptive matched filter, which are designed for homogeneous data exhibit significant performance degradation due to the non-Gaussianity and inhomogeneity of the sea clutter returns. To tackle this problem, we make use of the multichannel coherent single data set algorithm which removes the need for any training data, thus alleviating the problem of clutter heterogeneity. The algorithm performance is compared with traditional adaptive matched filter approaches using a Monte Carlo simulation with synthetic targets injected into a real multichannel data set.